Aortic coarctation in pregnancy: outcomes and predictors for cardiovascular and hypertensive complications. Data from the ESC Registry of Pregnancy and Cardiac disease (ROPAC). (25th November 2020) - Ramlakhan, K.P; Tobler, D; Greutmann, M; Schwerzmann, M; Baris, L; Yetman, A.J; Nihoyannopoulos, P; Manga, P; Boersma, H; Johnson, M.R; Hall, R; Roos-Hesselink, J.W
Abstract: Background: Pregnancy in women with repaired aortic coarctation (CoA) has a moderately increased risk (mWHO II-III) of an adverse cardiovascular, obstetric or fetal event, but prospective data to validate this estimated risk is scarce. Purpose: We examined maternal and fetal outcomes in pregnant women with unrepaired and repaired CoA to identify predictors of adverse outcomes. Methods: Pregnancies in women with CoA were selected from the worldwide prospective Registry of Pregnancy and Cardiac Disease (ROPAC, n=5739). The frequency and predictors of major adverse cardiac events (MACE, defined as maternal cardiac death, heart failure, atrial fibrillation/flutter, ventricular tachyarrhythmia, endocarditis, thromboembolic events, aortic dissection and acute coronary syndrome), and hypertensive complications (defined as pregnancy-induced hypertension, (pre)eclampsia or HELLP syndrome) were analyzed. Results: Of 303 pregnancies in women with CoA (median age 30 years, median pregnancy duration 39 weeks), 10% were in women with unrepaired CoA and 27% in women with pre-existing hypertension. There were no maternal deaths. There were 4 neonatal deaths of which 3 occurred after a spontaneous extreme preterm birth. MACE occurred in 4.3% of pregnancies, predominantly involving heart failure (3.3%). MACE rate was similar in unrepaired vs repaired CoA (3.4% vs 4.4%, p=0.814). Predictors of MACE included pre-pregnancy clinical signs of heart failure (OR 31.8, 95% CI 6.8–147.7), LVEF <40% (OR 10.4, 95% CI 1.8–59.5), NYHA class >1 (OR 11.4, 95% CI 3.6–36.3), cardiac medication use (OR 4.9, 95% CI 1.3–18.3) and living in an emerging country (OR 4.88, 95% CI 1.58–15.07). Hypertensive complications occurred in 6.3%, more often in the subgroup with pre-existing hypertension (11% vs 5%, p=0.040). Pre-existing hypertension was the only predictor (OR 2.6, 95% CI 1.01–6.6). Caesarean section was performed in 50% of the total cohort. Conclusions: Pregnancies in women with CoA are safe, well tolerated and MACE and hypertensive complication rates are low. These findings support mWHO risk score reevaluation to mWHO II for women with CoA without cardiac impairment. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): ESC EURObservational Research Programme (EORP)